2011
DOI: 10.4028/www.scientific.net/kem.467-469.1556
|View full text |Cite
|
Sign up to set email alerts
|

Measurements and Potential Applications of Force-Control Method for Stick-Slip-Driven Nanohandling Robots

Abstract: This paper describes the transition of a recently invented force-generation method to mobile nanohandling robots and outlines future applications. The presented mobile nanohandling robot makes use of miniaturized, piezo-driven Stick-Slip actuators. This allows for very accurate and fast positioning. The drives are fully developed and have proven their performance in fast pickand- place applications. On the other hand, the mentioned force-generation method allows a Stick- Slip axis to exert a dedicated force to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Controlled force generation with inertia motors has been investigated by Edeler et al [79,88,89]. These works have shown that in the investigated motor, the generated force-determined using the spring method-depends on a number of parameters, such as slider mass, friction contact, pre-load, and excitation signal.…”
Section: Force Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Controlled force generation with inertia motors has been investigated by Edeler et al [79,88,89]. These works have shown that in the investigated motor, the generated force-determined using the spring method-depends on a number of parameters, such as slider mass, friction contact, pre-load, and excitation signal.…”
Section: Force Generationmentioning
confidence: 99%
“…It was independently used as the basis of a specialised simulation technique for such motors by Hunstig et al ([87] (pp. [85][86][87][88][89][90][91][92][93]; [264]). …”
Section: High-frequency Operationmentioning
confidence: 99%
“…[3] and other fields. Piezoelectric actuators are widely used in many fields [4] such as nanorobotics [3,5], micro fixtures [6], in-situ testing [7], and precision positioning [8] due to their advantages of high accuracy, large stroke, and high stiffness [9]. Based on their operating principle, piezoelectric actuators are categorized into direct-acting and stepping types.…”
Section: Introductionmentioning
confidence: 99%